2006
DOI: 10.1093/toxsci/kfl079
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic (SELDI-TOF-MS) Approach to Estrogen Agonist Screening

Abstract: A small fish model and surface-enhanced laser desorption/ionization time-of-flight mass spectrometry were used to investigate plasma protein expression as a means to screen chemicals for estrogenic activity. Adult male sheepshead minnows (Cyprinodon variegatus) were placed into aquaria for seawater control, solvent control, and treatments of 17beta-estradiol (E2), methoxychlor (MXC), bisphenol-A (BPA), 4-tert-pentylphenol (TPP), endosulfan (ES), and chlorpyriphos (CP). Fish plasma was applied to weak cation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
6
23
0
Order By: Relevance
“…Similar to research on model species, the most commonly used method of protein separation in non-model species is 2DGE, although LC has been utilized in a few studies [6]. Tandem TOF/TOF is the most frequently used mass spectrometric setup in non-model proteomic research, but TOF analyzers coupled with quadropoles are not uncommon [33]. An FT-ICR mass analyzer coupled with an ion trap was also used in one study [31].…”
Section: Non-model Fish Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to research on model species, the most commonly used method of protein separation in non-model species is 2DGE, although LC has been utilized in a few studies [6]. Tandem TOF/TOF is the most frequently used mass spectrometric setup in non-model proteomic research, but TOF analyzers coupled with quadropoles are not uncommon [33]. An FT-ICR mass analyzer coupled with an ion trap was also used in one study [31].…”
Section: Non-model Fish Speciesmentioning
confidence: 99%
“…Surface-enhanced laser desorption ionization (SELDI)-TOF is a technique that exploits the chemical characteristics (e.g., hydrophobicity, charge) of proteins as a means of simplifying complex samples; SELDI-TOF does not enable one to identify differentially expressed proteins, but does yield information that may be helpful in identifying these proteins (peaks) of interest through subsequent tandem MS analysis. This technique has been used in at least two recent non-model studies [33,34], and was highlighted in another [3]. The isobaric tags for relative and absolute quantification (iTRAQ) approach was also used recently to quantitatively profile hepatic fathead minnow proteins involved in androgen receptor signaling [6].…”
Section: Non-model Fish Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study that employed SELDI-TOF MS with a weak cation exchange ProteinChip to analyze protein expression in hemolymph from field collected blue mussels (Mytilus edulis) exposed to crude oil, oil spiked with PAHs, or oil spiked with alkylphenols in the laboratory was able to classify masked samples with 90% to 95% accuracy . Other investigators demonstrated that either SELDI-TOF MS or MALDI-TOF MS could be used in conjunction with ProteinChip arrays to detect anonymous biomarkers of xenoestrogen exposure in plasma samples from adult male sheepshead minnows (Walker et al, 2007;Salinas et al, 2008). These studies represented progress toward developing a laboratory-based assay that could possibly evaluate multiple endocrine modes of action based on a single laboratory exposure.…”
Section: Protein Expression Signaturesmentioning
confidence: 99%
“…By the approach, over 40 proteins differentially expressed following exposure to a strong androgen, an antiandrogen, or a mixture of the two were identified, making it possible to conduct ontology-and pathway-based analyses similar to those commonly utilized in transcriptomic studies (Martyniuk et al, 2008). In addition to studies that are specifically mechanistic in orientation, a variety of proteomics studies aimed at PES and/or biomarker identification have determined the identities of at least some differentially expressed proteins, in some cases identifying sufficient numbers to facilitate ontology-and pathway-based analyses (Rodriguez-Ortega et al, 2003;Apraiz et al, 2006;Amelina et al, 2007;Walker et al, 2007). Finally, a few groups have employed proteomic approaches to examine alterations in protein modification associated with polluted versus reference field sites or laboratory exposures (McDonagh et al, 2005;McDonagh and Sheehan, 2007).…”
Section: Mechanistic Proteomics Researchmentioning
confidence: 99%